Gadget Use Duration, Sleep Quality, and Anaemia Among Adolescent Girls: A Cross-Sectional Study in Makassar, Indonesia - Suchi Avnalurini Sharief; Sitti Hadriyanti Hamang; Nurhayati Nurhayati (Pancasakti Journal Of Public Health Science And Research, 2026)
The increasing duration of gadget use among adolescent girls has raised concerns regarding its potential impact on sleep quality and nutritional health, including anaemia. Prolonged exposure to electronic screens may disrupt normal sleep patterns, which can interfere with physiological processes involved in haemoglobin synthesis. This study aimed to examine the association between gadget use duration, sleep quality, and anaemia among adolescent girls in Makassar, Indonesia. A cross-sectional study was conducted among adolescent girls in Makassar. Data on gadget use duration were collected using a structured questionnaire, while sleep quality was assessed using a validated sleep quality instrument. Haemoglobin levels were measured to determine anaemia status. Data were analysed using descriptive statistics and bivariate analysis to assess associations between variables. The results showed that a considerable proportion of participants reported prolonged gadget use, particularly more than three hours per day. Poor sleep quality was more common among adolescents with longer gadget use duration. Anaemia was identified in a notable proportion of participants. Statistical analysis revealed a significant association between gadget use duration and sleep quality, as well as between sleep quality and anaemia status. Adolescents with prolonged gadget use and poor sleep quality were more likely to experience anaemia. In conclusion, prolonged gadget use is associated with impaired sleep quality, which may increase the risk of anaemia among adolescent girls. These findings highlight the importance of promoting healthy gadget use habits and adequate sleep as part of anaemia prevention strategies in adolescent populations.